International Experience of Kazakhstan in Financing Small and Medium-Sized Enterprises: The Case of Malaysia (International relations and international law Journal, 2026)
In the context of contemporary geo-economic transformations and intensifying market rivalry across global arenas, scaling the small and medium enterprise sector serves as a vital strategic priority for Kazakhstan’s national economy. Consequently, there is an urgent academic and practical need for deep reflection upon advanced international institutional frameworks to establish highly effective mechanisms for the financial stimulation of domestic commerce. This research focuses on a comprehensive analysis of the Malaysian model concerning fiscal and credit support for small and medium businesses, identifying key pathways to adapt these successful instruments within Kazakhstan’s economic reality. The study thoroughly dissects the operational parameters of public development institutions in Malaysia, commercial banking frameworks, the “Pioneer Status” tax preference regime, alternative Islamic finance products, and the specialized credit infrastructure of the “SME Bureau”. The practical value of this paper lies in formulating actionable and structured recommendations to overhaul entrepreneurship support policies in Kazakhstan and upgrade the tools currently utilized in domestic state-run development programs. Methodologically, the paper relies extensively on systemic, comparative economic, and structural-functional analysis. As a result, the structural efficiency of Malaysia’s synergy-based financial tools is fully demonstrated, providing an author-designed algorithm for their introduction while heavily considering Kazakhstan’s unique socio-economic landscape and institutional gaps. The insights gained offer a practical foundation for updating national frameworks.Keywords: small and medium-sized enterprises, Malaysia, fiscal support, credit support, Pioneer Status, Islamic finance, comparative analysis.